Dapagliflozin‐Loaded Exosome Mimetics Facilitate Diabetic Wound Healing by HIF‐1α‐Mediated Enhancement of Angiogenesis. Issue 7 (12th December 2022) - Zhang, Weiyue; Wang, Lutong; Guo, Haoyu; Chen, Lulu; Huang, Xin
Abstract: Angiogenesis plays a critical role in diabetic wound healing. However, no effective strategies have been developed to target endothelial cells (ECs) to facilitate diabetic wound healing. Dapagliflozin (DA) as a sodium‐glucose linked transporter 2 (SGLT2) inhibitor, may promote neovascularization in diabetic mice via HIF‐1 α ‐mediated enhancement of angiogenesis. Here, the bioinspired nanovesicles (NVs) prepared from induced pluripotent stem cells‐derived ECs through an extrusion approach are reported, which can function as exosome mimetics to achieve targeted deliver of DA. Abundant membrane C‐X‐C motif chemokine receptor 4 conferred the EC‐targeting ability of these NVs and the endothelial homology facilitated the accumulation in ECs. Furthermore, these DA‐loaded induced pluripotent stem cells (iPSC)‐EC NVs can facilitate angiogenesis and diabetic wound healing by HIF‐1 α /VEGFA pathway. Taken together, this study indicated that targeting ECs and regulating angiogenesis may be a promising strategy for the treatment of diabetic wound healing. Abstract : Bioinspired nanovesicles (NVs) are prepared from human induced pluripotent stem cells‐derived endothelial cells (iPS‐EC) through an extrusion approach, which functions as exosome mimetics to targeted deliver dapagliflozin (DA). These DA‐loaded iPS‐EC NVs facilitate angiogenesis and wound healing by the HIF‐1 α /VEGFA pathway, which may be a promising strategy for the treatment of diabetic wound healing.